OPTIMIZATION OF THE FORMULATED FEEDING IN JUVENILE CORAL TROUT, Plectropomus leopardus IN CONTROLLED TANK - Anak Agung Alit; Ketut Maha Setiawati; Tony Setiadharma (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
A coral trout grouper is the fishery commodities to generate foreign exchange through exports, to date cultivation continued. The purpose is to obtain data and information on the dose of the right artificial feeding and can increase the survival rate of the optimum seed nursery in the juvenile coral trout in controlled tank. Research has been conducted at the hatchery and the Institute for Mariculture Reasearch and Development Gondol, Bali. Containers experiment is used is a fiber with a size of 1 m³ up to 12 containers. test animals used were seeds of coral trout, Plectropomus leopardus with initial body length on average 3 cm with each treatment density of 100 fish/m³. Coral trout, Plectropomus leopardus seed kept in fibers. This type of feed given in the form of commercial pellet feed with a protein content of 48%, and additional food such as shrimp Mysid (jembret) for 10 days. The frequency of feeding 3 times a day (morning 8:00. local time, lunch 13:00 local time, and afternoon 17:00 local time). Treatment feeding attempted is the treatment of A = 5% dose of artificial feeding, B = 10% dose of artificial feeding, C = 15% dose of artificial feeding, and D = 20% dose of artificial feeding. The study used a completely randomized design with 4 treatments, each treatment was repeated 3 times. Data were analyzed by analysis of variance. If the variance is different then conducted a further test using the smallest real difference test (BNT). The results showed that significantly different (P <0.05) on survival, feed conversion, weight gain and body length of coral trout. The highest survival rate in treatment C = 15% dose artificial feeding is. = 90.83 ± 1.80%, followed by treatment D, B, and A.